THE CONCEPT, CHARACTERISTICS OF CORPORATE-TYPE LEGAL ENTITIES (CORPORATIONS) AND DESCRIPTION OF GOVERNING BODIES - Meliksetyan, Karen (State and Law, 2023)
This scientific work is devoted to the study of the essence and features of corporate-type legal entities (corporations), identifying the distinctive features of corporate-type and non-corporate legal entities, identifying the characteristics and content of corporate governance bodies. The paper studied the legislative regulations of a number of domestic and foreign countries concerning corporations and their features, practice, as well as the works of theoretical scientists. As a result of the above, the concept of corporations and the features of the latter were formulated. In the work, the system of corporate governance bodies and its individual components with their inherent features and classifications were identified and analyzed. In the study of foreign and, first of all, American legislation regarding venture funds (including angel investors) and venture capital, it was proposed, by analogy with the C Corp corporations operating in the United States, to introduce the concept of venture joint stock companies as a special kind of joint stock companies, taking into account a number of characteristics․